Preparation and Application of Dual-Crosslinked Compressible Expandable Aerogel Dressing - Bari, Abu; Akter, Rahman (Journal of Green Energy and Environmental Engineering, 2024)
Medical dressings are critical materials for wound care, effectively promoting wound healing and alleviating patient suffering. With social development and improved living standards, higher functional requirements for medical dressings have emerged. In areas such as sensitive wound care and cavity bleeding, elastic and expandable dressings play vital roles. Aerogel dressings, characterized by their three-dimensional porous structure, low density, high porosity, and high specific surface area, offer significant advantages. Currently, polyurethane aerogels are the most commonly used functional aerogel dressings. However, their preparation heavily relies on petroleum-derived chemicals such as methylene diphenyl diisocyanate and toluene diisocyanate, resulting in high production costs, high prices, and poor degradability, which limit their widespread application. Natural polymers, as important biomass materials, offer advantages such as wide availability, excellent biocompatibility, and soil degradability. Amidst increasing petroleum resource shortages and environmental concerns, it is urgent to develop natural polymer aerogel dressings with tailored structures and properties to achieve green iterative upgrades of functional aerogel dressings. This study utilizes sodium carboxymethyl cellulose (CMC), hydroxypropyl cellulose (HPC), and coniferous pulp (CP) as raw materials. Through dual physical and chemical crosslinking strategies, combined with ice-templating, pore-forming agents, and foaming agents, a multi-level porous structure was constructed to prepare CMC-CP dual-crosslinked compressible expandable aerogel dressings. The structure and properties of the resulting aerogel dressings were tested and analyzed. The results indicate that heating promotes glutaraldehyde (GA) to form covalent bonds between CMC and CP, achieving chemical crosslinking. The introduction of HCl protonates the sodium carboxylate groups of CMC into carboxyl groups. Using a foaming agent (SDS), the mixture is fully foamed. Freezing facilitates hydrogen bonding for physical crosslinking and leverages the synergistic pore-forming effects of the foaming agent and ice-templating. After freeze-drying, an aerogel dressing with a hierarchical porous structure is obtained. The CMC-CP dual-crosslinked compressible expandable aerogel dressing exhibits high strength, excellent compressibility, and liquid-absorption expansion properties. Compared to gelatin sponges and medical gauze, the aerogel dressing demonstrates good in vitro cytocompatibility, indicating its promising application potential and practical value as a wound dressing.